Answer:
The weight of the astronaut on the surface of moon due to the force of gravitation becomes one-sixth of the size of the gravitational acceleration on Earth.
Step-by-step explanation:
Let the mass of the astronaut is, m = M
The acceleration due to gravity on Earth is, a = g
The acceleration due to gravity on the moon is a' = g/6
The weight of the astronaut on Earth, W = Mg
The weight of the astronaut on the moon is, w = Mg/6
W = w /6
Hence, the weight of the astronaut on the surface of moon due to the force of gravitation becomes one-sixth of the size of the gravitational acceleration on Earth.